2021
DOI: 10.1155/2021/5555028
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acupuncture on Glucose Metabolism and Lipid Profiles in Patients with PCOS: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Objective. To evaluate the effectiveness of acupuncture on glucose metabolism and lipid profiles in patients with polycystic ovary syndrome (PCOS). Methods. Databases, including the China National Knowledge Infrastructure (CNKI), the China Science and Technology Journal Database (VIP), Wanfang, PubMed, and the Cochrane Library were searched for the relevant literature, with the retrieval deadline being February 2020. Two reviewers independently screened, selected, and extracted the data and validated the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The findings of Wu et al (2017) did not support acupuncture as an infertility treatment in anovulatory women with PCOS. Systematic reviews and some studies have demonstrated that electroacupuncture has the potential to increase whole-body glucose uptake and to improve insulin sensitivity through the activation of the sympathetic and, partly, the parasympathetic nervous systems in women with PCOS or in animal models ( Liang and Koya, 2010 ; Benrick et al , 2017 ; Zheng et al , 2021 ). Our prospective pilot studies showed that acupuncture also has a significant effect on the homeostatic model assessment of insulin resistance (HOMA-IR) in women with PCOS and IR after 5 weeks, and after 6 months of treatment ( Zheng et al , 2015 ; Stener-Victorin et al , 2016 ; Li et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of Wu et al (2017) did not support acupuncture as an infertility treatment in anovulatory women with PCOS. Systematic reviews and some studies have demonstrated that electroacupuncture has the potential to increase whole-body glucose uptake and to improve insulin sensitivity through the activation of the sympathetic and, partly, the parasympathetic nervous systems in women with PCOS or in animal models ( Liang and Koya, 2010 ; Benrick et al , 2017 ; Zheng et al , 2021 ). Our prospective pilot studies showed that acupuncture also has a significant effect on the homeostatic model assessment of insulin resistance (HOMA-IR) in women with PCOS and IR after 5 weeks, and after 6 months of treatment ( Zheng et al , 2015 ; Stener-Victorin et al , 2016 ; Li et al , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture harmonizes the "Yin" and "Yang" and dredges the channels of "Qi" and "Blood" for treating diseases. Due to its safety and few side effects, acupuncture has been well-received in treating various diseases and symptoms, especially chronic metabolic illnesses [26,27] , and acupuncture has been reported to be a relatively effective and safe method for improving glucose metabolism and insulin sensitivity in patients with PCOS [28] . EA effectively ameliorated abdominal obesity and metabolic disorders in HFD-induced abdominally obese rats [29] , and clinical trials have indicated that EA can decrease the levels of ALT, AST, and TG in female patients suffering from nonalcoholic fatty liver disease, suggesting that this approach might be an important treatment for improving liver functions in these patients [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Correlation meta-analysis has shown that acupuncture has a beneficial effect on IR and fewer adverse reactions than other treatments [6,7]. A recent meta-analysis also found that acupuncture can improve IR in patients with PCOS [8]. However, this evidence is inadequate because of the poor quality and methodology of the included studies.…”
Section: Introductionmentioning
confidence: 99%